1997
DOI: 10.1074/jbc.272.15.9971
|View full text |Cite
|
Sign up to set email alerts
|

The Glycosaminoglycan Binding Site Governs Ligand Binding to the Somatomedin B Domain of Vitronectin

Abstract: The ligand binding functions of vitronectin (Vn) are regulated by its conformational state/degree of multimerization. In the native plasma form of Vn, the C-terminal glycosaminoglycan (GAG) binding domain is believed to be cryptic. Here, evidence is provided that the addition of fucoidan or dextran sulfate to unfractionated plasma results in the formation of covalently and non-covalently stabilized Vn multimers. These multimers express conformationally sensitive antibody epitopes and ligand binding sites locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 31 publications
3
26
0
Order By: Relevance
“…Our results show that for heparin, the CD34 + culture outcomes ranged from minimal proliferation to extensive proliferation to full toxicity as a function of the heparin levels. This concentration effect is supported by reports that variations in GAG levels may play a significant role in the regulation of hematopoiesis [30,31]. Notably, the activities of IL-3 and GM-CSF were shown to increase as the concentration of heparan sulfate increased [30].…”
Section: Discussionsupporting
confidence: 65%
“…Our results show that for heparin, the CD34 + culture outcomes ranged from minimal proliferation to extensive proliferation to full toxicity as a function of the heparin levels. This concentration effect is supported by reports that variations in GAG levels may play a significant role in the regulation of hematopoiesis [30,31]. Notably, the activities of IL-3 and GM-CSF were shown to increase as the concentration of heparan sulfate increased [30].…”
Section: Discussionsupporting
confidence: 65%
“…Studies in other laboratories have indicated that multimerization of proteins can alter their ligand-binding capacity (Oh et al, 1997;Seiffert, 1997). We thus decided to test the effect of removing the Ena EVH2 domain on its affinity for the Abl-SH3 domains and zyxin.…”
Section: The Evh2 Domain Is Important For Ena's Ability To Bind the Amentioning
confidence: 99%
“…interacts with a wide variety of ligands and is involved in cell-ECM adhesion, cell differentiation and proliferation, and blood coagulation, and is an inhibitor of complement pathway(s) (Seiffert, 1997;Preissner and Seiffert, 1998). Two forms of vitronectin exist under physiological conditions, with most of the circulating pool of vitronectin in a native (monomeric) form (M r 75 kDa), whereas the multimeric form of vitronectin is found predominantly in the ECM or is tissue associated (Stockmann et al, 1993).…”
Section: Ingestion Of Pneumococci By Host Cells Via Vitronectin Requimentioning
confidence: 99%